1995
DOI: 10.1021/j100012a017
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Nbn+ (n = 2-6) with Ethylene in the Gas Phase: Collision-Induced Dissociation Studies of Ionic Products

Abstract: The gas-phase reactions of Nb,+ (n = 2-6) with C2& are studied by Fourier transform mass spectrometry. Collision-induced dissociation (CID) and ion-molecule reactions are used to probe the product ion structures.The sequential reactions of N b 2 + are believed to involve ligand coupling, while for the larger clusters this mechanism is less important. The bonding between the Nb atoms and the C atoms of the ligand in the product ions becomes stronger with increasing cluster size. One of the major product ions fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…Parameters for the Morse function called Morse*1 were chosen so that Morse*1 gives the following: (1) an Ar + Al 6 (O h ) energy transfer probability distribution and CID cross section versus E rel in near exact agreement with those for the above L-J/A-T potential; (2) potential. Parameters for the Morse function called Morse*1 were chosen so that Morse*1 gives the following: (1) an Ar + Al 6 (O h ) energy transfer probability distribution and CID cross section versus E rel in near exact agreement with those for the above L-J/A-T potential; (2) potential.…”
Section: Cluster Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parameters for the Morse function called Morse*1 were chosen so that Morse*1 gives the following: (1) an Ar + Al 6 (O h ) energy transfer probability distribution and CID cross section versus E rel in near exact agreement with those for the above L-J/A-T potential; (2) potential. Parameters for the Morse function called Morse*1 were chosen so that Morse*1 gives the following: (1) an Ar + Al 6 (O h ) energy transfer probability distribution and CID cross section versus E rel in near exact agreement with those for the above L-J/A-T potential; (2) potential.…”
Section: Cluster Modelsmentioning
confidence: 99%
“…Collision-induced dissociation (CID) of cationic clusters with rare gases have been used to study dissociation mechanisms 1 and bond energies for the clusters. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The CID cross section is measured versus the cluster-rare gas relative translational energy, and the bond dissociation energy for the cluster has been estimated from the CID threshold E o CID .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of reactions of different metal cluster ions has been reported in the literature . In particular, several studies have been performed on niobium clusters, including reactions with H 2 , N 2 , O 2 , CO, CO 2 , BrCN, and some selected organic compounds. The trends in the reaction rates, ,, reaction saturation limits, and, for some organic molecules, the degree of dehydrogenation (or conversion probability) 11-14 have been investigated. In our previous study on the reactions of Nb n + ( n = 2−13) with ethene, it was found that the reaction efficiency and the degree of dehydrogenation jumped from Nb 2 + to Nb 3 + .…”
Section: Introductionmentioning
confidence: 99%
“…As a first step in trying to understand this behavior, we have investigated the dissociation behavior of ammonia on a pure Nb surface. Recently, several studies on small Nb clusters have shown that Nb can be highly reactive with H 2 , H 2 O, and a variety of hydrocarbon compounds. , Goodwin and Salahub employed a density functional approach to study the binding energies and bond dissociation energies for small Nb clusters and achieved good agreement with experimental results . To understand the role of Nb in alloy surfaces in nitriding process, we utilized the DFT approach to study the chemisorption structures and energetics of the nitriding species.…”
Section: Introductionmentioning
confidence: 95%